Steroidogenic differentiation of human amniotic membrane-derived mesenchymal stem cells into a progesterone-/androgen-producing cell lineage by SF-1 and an estrogen-producing cell lineage by WT1−KTS - Miyazaki, Yumiko; Orisaka, Makoto; Fujita, Yuko; Mizutani, Tetsuya; Yazawa, Takashi; Yoshida, Yoshio (Frontiers in Endocrinology, 2024)
Background Sex steroid hormones, primarily synthesized by gonadal somatic cells, are pivotal for sexual development and reproduction. Mice studies have shown that two transcription factors, steroidogenic factor 1 (SF-1) and Wilms’ tumor 1 (WT1), are involved in gonadal development. However, their role in human gonadal somatic differentiation remains unclear. We therefore aimed to investigate the roles of SF-1 and WT1 in human gonadal steroidogenic cell differentiation. Methods Using a transient lentivirus-mediated gene expression system, we assessed the effects of SF-1 and WT1 expression on the steroidogenic potential of human amniotic membrane-derived mesenchymal stem cells (hAmMSCs). Results SF-1 and WT1−KTS, a splice variant of WT1, played distinct roles in human steroidogenic differentiation of hAmMSCs. SF-1 induced hAmMSC differentiation into progesterone- and androgen-producing cell lineages, whereas WT1−KTS promoted hAmMSC differentiation into estrogen-producing cell lineages. Conclusion Our findings revealed that SF-1 and WT1−KTS play important roles in human gonadal steroidogenic cell differentiation, especially during ovarian development. These findings may pave the way for future studies on human ovarian differentiation and development.